Intellibin 1.0: A Prototype Of An Automated Smart Recycling Bin For Sustainable Waste Management - Khairul Asyraaf Khairul Azwan; Wan Muhammad Fahyim Wan Mohd Nazdi; Faqihah Imtiaz Mohamad Fadzil; Hannah Safiya Mohd Muharir; Ts. Dr. Hatika Kaco (Kolej PERMATA Insan, 2025)
Insan Junior Researcher International Conference & Innovation (iJURECON) 2025 : “STREAM for a Better Future/ editor : Ahmad Fuad Mohamad Amin, Nurul Shazwani Binti Mohamed, Rossidi Bin Usop, Abdel Rahman Ibrahim Suleiman Islieh Organised by Kolej PERMATA Insan 10-11 October 2025